Methodologies to Assess the Biodegradability of Bio-Based Polymers—Current Knowledge and Existing Gaps - Pires, João Ricardo Afonso (2022)
Our society lives in a time of transition where traditional petroleum-based polymers/plastics are being replaced by more sustainable alternative materials. To consider these bioproducts as more viable options than the actual ones, it is demanded to ensure that they are fully biodegradable or compostable and that there is no release of hazardous compounds to the environment with their degradation. It is then essential to adapt the legislation to support novel specific guidelines to test the biodegradability of each biopolymer in varied environments, and consequently, establish consistent data to design a coherent labeling system. This review work aims to point out the current standards that can serve as a basis for the characterization of biopolymers’ biodegradation profile in different environments (soil, compost, and aquatic systems) and identify other laboratory methodologies that have been adopted for the same purpose. With the information gathered in this work, it was possible to identify remaining gaps in existing national and international standards to help establish new validation criteria to be introduced in future research and policies related to bioplastics to boost the sustainable progress of this rising industry.